Self-imaging of molecules from diffraction spectra by laser-induced rescattering electrons - Xu, Junliang; Chen, Zhangjin; Le, Anh-Thu; Lin, C. D. (My University, 2010)
We study high-energy angle-resolved photoelectron spectra of molecules in strong fields. In an oscillating laser electric field, electrons released earlier in the pulse may return to recollide with the target ion, in a process similar to scattering by laboratory prepared electrons. If midinfrared lasers are used, we show that the images generated by the returning electrons are similar to images observed in typical gas-phase electron diffraction (GED). These spectra can be used to retrieve the positions of atoms in a molecule as in GED. Since infrared laser pulses of durations of a few femtoseconds are already available today, the study of these high-energy photoelectrons offers the opportunity of imaging the structure of transient molecules with temporal resolution of a few femtoseconds.